METHODS OF ANALYSIS OF STOCK MARKETS - URBANIKOVA, Marta (Trends in education, 2010)
The article deals with the methods of analysis of stock markets. Share index is considered to be the indicator of the development of the stock markets. Besides some wellknown methods, methods of artificial intelligence are used for the analysis of the share index.
Keywords: Technical analysis; Fundamental analysis; Stock market index; Time series; Neural networks.